Designing Storylines for Children’s Mathematics Digital Interactive Storybook using Software Engineering Approach - Zainudin, Nurhamizah; Ismail, Azniah (Journal of ICT in Education, 2020)
Abstract This paper presents an early part of designing process for a math interactive storybook application prototype with 3D pop-up and augmented reality features. This application is designed using the evolutionary prototype model where we are required to have several complete 4-phases prototype model cycles. Several iterations were conducted specially to focus on getting the best storylines for a mathematics learning tool that involves 3D pop-up and augmented reality features. The process is still on-going. We will also validate with experts the storyline and the suitability of the story with the mathematic topics chosen. Once the design is validated, we will continue building the prototype andvalidate it with potential users until all features are satisfied. It is hoped that later this application will be accepted as an interesting learning tool and contribute as an educational learning resource for children.